The RFLP mapping of the calmodulin gene of Neurospora crassa - Yutaka Sadakane; Kiyoshi Onai; Masashi Akiyama; Hideaki Nakashima (Fungal Genetics Reports, 1996)
The map position of the calmodulin gene (cmd) was determined by RFLP (Restriction Fragment Length Polymorphism) mapping in Neurospora crassa. The cmd gene was mapped on chromosome V, between al-3 and inl.